High Temperature Inflammation and Combustion of Methane - Afonina Н.Е. (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2018)
The results of numerical simulation of the process of ignition of methane-oxygen mixtures diluted with nitrogen in the temperature range (700-2500) K for various compositions and pressures of the initial mixture are presented. The signs of ignition of the mixtures and the method of recording the induction time are indicated. The lower boundaries of the high-temperature range, in which the ignition of methane occurs in the chain branching mode of active radicals, are determined.